2017
DOI: 10.1111/ene.13523
|View full text |Cite
|
Sign up to set email alerts
|

OnabotulinumtoxinA in chronic migraine: predictors of response. A prospective multicentre descriptive study

Abstract: This study confirmed the effectiveness of treatment with OnabotulinumtoxinA after 1 year of treatment. The chances of a good outcome may be increased by starting treatment in the first 12 months after chronic migraine diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
64
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 39 publications
9
64
6
Order By: Relevance
“…However, this is not always easy due to the delay in diagnosis or in reaching specialized headache units . Other studies have found the time of migraine chronification as an important point to consider, without it being statistically significant in our study. One of the reasons for this difference, could be that the time of chronification of our cohort is much higher than that of the Dominguez et al study.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…However, this is not always easy due to the delay in diagnosis or in reaching specialized headache units . Other studies have found the time of migraine chronification as an important point to consider, without it being statistically significant in our study. One of the reasons for this difference, could be that the time of chronification of our cohort is much higher than that of the Dominguez et al study.…”
Section: Discussioncontrasting
confidence: 63%
“…However, we did not consider that this missingness could have a significant biasing effect in the results presented because discontinuation and treatment response rate were quite similar to published data: In the PREEMPT clinical trials, we observed that a 13.2% of patients discontinued from the trials (similar proportions of patients than in our data, 13.7%) and the change from baseline in monthly headache frequency at week 24 were also equivalent in both studies (PREEMPT: −8.3 days/month, this study: −9.1 days/month). Regarding the response rate, 75% response rate was not calculated in the PREEMPT but Dominguez et al work, the excellent response at month 12 was 27.3% (25.3% in our data).…”
Section: Discussioncontrasting
confidence: 58%
“…In addition, our study could help answer common questions in daily clinical practice regarding the decision on when to stop treatment with onabotulinumtoxinA due to its efficacy or futility. Moreover, our results add information to the current knowledge of treatment in real life with onabo-tulinumtoxinA; mainly [15] treating early after migraine becomes chronic is a clinical predictor of good response; the initial gain (6 months) is based on frequency and the improvement at mid to long term is based on pain intensity, leading, with a good preventative treatment, to a controlled evolution of the natural cycles of migraine.…”
Section: Discussionmentioning
confidence: 60%
“…Such vulnerability is most concerning for patients with CM who may be more susceptible to CS compared to patients with episodic migraine. 13,16,45 This phenomenon may be related to a lapse in duration of effect because of the standard 12-week injection interval used in the studies. By providing a sustained therapeutic effect from optimal injection cycle durations, the goal of suppression of CS can be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, BoNTA has a dual mechanism of action with effects on sensory and motor nerves. [13][14][15][16] Of note, 2 large studies on the use of BoNTA for chronic daily headaches adopted an injection interval of 90 days. [5][6][7][8][9][10] Compared to other pharmacologic prophylactic therapies, onabotu-linumtoxinA is beneficial, for it does not require daily dosing and is not associated with common cognitive side effects.…”
Section: Introductionmentioning
confidence: 99%